2019
DOI: 10.1074/jbc.rev119.007963
|View full text |Cite
|
Sign up to set email alerts
|

Control of cellular responses to mechanical cues through YAP/TAZ regulation

Abstract: To perceive their three-dimensional environment, cells and tissues must be able to sense and interpret various physical forces like shear, tensile, and compression stress. These forces can be generated both internally and externally in response to physical properties, like substrate stiffness, cell contractility, and forces generated by adjacent cells. Mechanical cues have important roles in cell fate decisions regarding proliferation, survival, and differentiation as well as the processes of tissue regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
190
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(215 citation statements)
references
References 137 publications
1
190
0
2
Order By: Relevance
“…We did, however, examine the mechano‐sensing mechanism induced in response to growth on the XG‐LBG substrate. In general, stiffness is detected by focal adhesion or contraction of the cells, and the cytoskeleton plays a major role in signal transduction (Dasgupta & McCollum, 2019). In addition, increased expression of the genes associated with the focal adhesion pathway is one of the most important distinguishing features between in vivo‐developed blastocysts and in vitro ‐ developed blastocysts in cows (Noguchi, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We did, however, examine the mechano‐sensing mechanism induced in response to growth on the XG‐LBG substrate. In general, stiffness is detected by focal adhesion or contraction of the cells, and the cytoskeleton plays a major role in signal transduction (Dasgupta & McCollum, 2019). In addition, increased expression of the genes associated with the focal adhesion pathway is one of the most important distinguishing features between in vivo‐developed blastocysts and in vitro ‐ developed blastocysts in cows (Noguchi, et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, XG‐LBG gel increased F‐actin expression levels and improved localization of E‐cadherin. These cytoskeletal elements regulate nuclear YAP localization through complex feedback loops including mechanical connections between the cytoskeleton and nucleus, nuclear flattening, and actin‐associated inactivation of LATS induces the nuclear import of YAP (Dasgupta & McCollum, 2019; Elosegui‐Artola et al., 2017). This study showed that culturing embryos on XG‐LBG increased nuclear‐expression levels of YAP and increased downstream CTGF protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Der Verlust der PTH1R-Expression in osteogenen Zellen hemmt die Mechanosensitivität, und eine neuere klinische Studie kommt zu dem Ergebnis, dass die Kombination aus mechanischer Stimulation und Teriparatid mit Blick auf den Gewinn an Knochenmasse wesentlich effektiver ist als Teriparatid alleine [47,48]. Aber auch für die "neueren" starken Modulatoren der osteogenen Differenzierung in Entwicklung und Regeneration wurde in jüngster Zeit von unserer Arbeitsgruppe und anderen nachgewiesen, dass sie durch mechanische Reize moduliert werden können [49][50][51][52][53]. Insofern ist alleine die Übertragung physikalischer Kräfte durch Muskelaktivität ein plausibler und gut belegter Mechanismus der Interaktion zwischen Muskel und Knochen.…”
Section: Osteogene Signalwege Und Ihre Interaktion Mit Mechanischer Sunclassified